ChemInform Abstract: Amberlite IR‐120 Catalyzed, Microwave‐Assisted One‐Pot Synthesis of Amides from Nitriles by Ritter Reaction. Issue 48 (2nd December 2014) - Ghasemnejad‐Bosra, Hassan; Habibzadeh, Setareh
Abstract A highly efficient method for the synthesis of α‐arylethyl amides from styrenes and related alcohols using the Ritter reaction is developed.